A Methods engineering study on Mandaluyong Pottery - Cando, Kim E. (College of Engineering, 2002)
Mandaluyong Pottery is a small company that manufactures different kinds of pots. It regularly supplies various garden and flower shops in Metro Manila. It is a company whose prime concerns are to make sure the orders of the customers are met and ensure that enough materials are available. In the hope of helping the company improve its current situation, the group analyzed the Mandaluyong Pottery system : its systems and procedures, its production activities, and its work flow and layout. Time study was utilized to find the standard times for the different tasks and help the group identify problem areas. Problem identification, problem analysis and prioritization showed that the problem areas were the baking process, transport, handling and storage of materials and works in process, its workflow and layout and its poor working conditions. Knowing what the problems of the company were, the group began to generate alternatives to the company's existing procedures, equipment and practices. Recommendations were made to improve the baking process. A baking program was presented and improvements to the existing ovens were suggested. The transport equipment was studied and alternatives were also presented. The plant layout was modified to lessen distances between workstations and reduce travel time. Improvements in the plant's working conditions were endorsed. Lighting and ventilation were improved and safety measures were introduced. Through the analysis performed, the group believed that recommendations presented to the company could help Mandaluyong Pottery improve its situation. The group therefore recommended that the company look into the proposals and analyze the advantages and disadvantages that they might bring. Should the company decide to accept the proposals, it should incorporate them into its short term and long term plans.